Pain Practice Volume 16 Number 2 February 2016 - Tim Editor (Wiley-Blackwell, 2016)
-Enhancement of analgestic effect by combination of non-noxious stimulation and noxious stimulation in humans -The impact of a national guidline on the management of cancer pain on the practice of pain assessment and registration -Twelve-month follow-up of the patient health questionnaire as a screener for psychiatric comorbidity in a chronic disabling occupational musculoskeletal disorder population -...